Treatment of refractory epilepsy with natalizumab in a patient with multiple sclerosis. Case report - Constantin Gabriela; Murrighile Maria R; Sotgiu Stefano (BMC Neurology, 2010)
Abstract Background Multiple sclerosis (MS) is considered an autoimmune disease of the central nervous system and therapeutic inhibition of leukocyte migration with natalizumab, an anti-alpha4 integrin antibody, is highly effective in patients with MS. Recent studies performed in experimental animal models with relevance to human disease suggested a key role for blood-brain barrier damage and leukocyte trafficking mechanisms also in the pathogenesis of epilepsy. In addition, vascular alterations and increased leukocyte accumulation into the brain were recently documented in patients with refractory epilepsy independently on the disease etiology. Case report Here we describe the clinical course of a 24-year-old patient with MS in whom abrupt tonic-clonic generalized seizures manifested at disease onset. Although MS had a more favorable course, treatment with glatiramer acetate and antiepileptic drugs for 7 years had no control on seizure generation and the patient developed severe refractory epilepsy. Interestingly, generalized seizures preceded new MS relapses suggesting that seizure activity may contribute to MS worsening creating a positive feedback loop between the two disease conditions. Notably, treatment with natalizumab for 12 months improved MS condition and led to a dramatic reduction of seizures. Conclusion Our case report suggests that inhibition of leukocyte adhesion may represent a new potential therapeutic approach in epilepsy and complement the traditional therapy with anti-epileptic drugs.